Microencapsulation of betanins by spray drying with mixtures of sweet potato starch and maltodextrin as wall materials to prepare natural pigments delivery systems. Issue 4 (10th February 2022) - Esquivel‐González, Blanca Edith; Medina‐Torres, Luis; Ochoa‐Martínez, Luz Araceli; Rutiaga‐Quiñones, Olga Miriam; Rocha‐Guzmán, Nuria E.; Calderas, Fausto; Varela‐Santos, Elizabeth del Carmen
Abstract: The potential use of maltodextrin (MD) and sweet potato starch (SPS) mixtures to encapsulate betacyanine from a beetroot extract by the spray‐drying (SD) process was studied. As the SPS content increased in the mixtures, the powder recovery, moisture content, hygroscopicity, porosity, and solubility increased, whereas the values of wettability decreased. The encapsulated betacyanine content increased with the content of SPS in the mixtures, increasing antioxidant activity. The reconstituted powders of MD/SPS mixtures in water showed non‐Newtonian shear‐thinning and a predominant viscous behavior in the rheological tests, except for the sample with 100% SPS, which showed characteristics of a gel. The morphology of the microparticles was shown to depend on the SPS content with a tendency of the particles to aggregate FT‐IR analysis showed that the signals of specific groups of betanins were diminished, which is evidence of the microencapsulation of the betanins, and this was corroborated by transmission electronic microscopy. Practical applications: Nowadays, the use of mixtures of biopolymers as encapsulating wall materials is highly appreciated by the food and pharmaceutical industries. This research demonstrated that mixtures of sweet potato starch and maltodextrin at different content ratios are suitable for the microencapsulation of betanins to prepare natural pigments delivery systems with potential applications in functional foods, antioxidants systems, and pharmaceuticals. These systems were characterized by several techniques such as rheology, morphology, FT‐IR, and antioxidant activity in this work. Results of this investigation may help to develop new pigment systems, with potential application as bioactive compounds. Increasing health benefits, including probiotic effects, are expected with the intake of these antioxidants.